1999
DOI: 10.1177/001872679905201106
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Management Through Participation in Sport and Physical Activity: Experiences of Male College Students with Physical Disabilities

Abstract: Individuals with physical disabilities are often stigmatized because their bodies are assumed to vary from norms of physical competence and bodily appearance. Possession of a discrediting attribute may impair social interactions and result in the devaluation of an individual. The purpose of this paper is to explore how involvement in sport and physical activity may be one strategy to manage the stigma of a disabled body. Data were collected through in-depth interviews with 24 male college students with physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 16 publications
3
50
0
2
Order By: Relevance
“…This corresponds with FraserThomas and Côté's (2009) finding that coaches' belief in their athletes can positively influence athletes' self-efficacy and continued motivation towards sport. This pathway may be of particular importance since athletes with disabilities often perceive that others have low expectations of their capabilities (Taub, Blinde, & Greer, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with FraserThomas and Côté's (2009) finding that coaches' belief in their athletes can positively influence athletes' self-efficacy and continued motivation towards sport. This pathway may be of particular importance since athletes with disabilities often perceive that others have low expectations of their capabilities (Taub, Blinde, & Greer, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research allows for a more insightful look in identifying what problems disabled individuals have, mainly by allowing participants to freely express themselves unencumbered by research restrictions. In addition, it provides a broader context of the difficulties that arise in the lives of those who are disabled [7,13].…”
Section: Methodsmentioning
confidence: 99%
“…Sport and physical activity can also be a great form of stimulating personal development and empowerment. Numerous studies conducted on persons with a disability suggested that participation in organized sports had a positive effect on mood and self-efficacy and contributed to the growth of individual empowerment [6,7]. Sport also provides a number of opportunities for learning new skills, taking risks, reducing the risk of disease and helps build and maintain social relationships and networks [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…attributions (Taub, Blinde, & Greer, 1999) and consensually held stereotypes (NarioRedmond, 2010). To protect the self from such negative characterizations, one may seek to increase the permeability of the boundary between ''disabled'' and ''nondisabled'' groups via direct medical intervention to eliminate impairments thereby escaping disability.…”
Section: Coping With Disability Stigma: Individualistic and Collectivmentioning
confidence: 99%